Force-Chain-Based Analysis of Factors Influencing Pressure Arch Around Tunnel Under Earthquake - Changxin, Sun; Yumin, Zhang; Lei, Guan; Liye, Zhang; Jiafeng, Peng (Frontiers in Earth Science, 2022)
The force chain method is a powerful tool to analyze the pressure arch of a tunnel, which has important influence on the seismic stability of tunnel structures. The force distribution around the tunnel before and after an earthquake was observed with numerical simulation and shaking table test, and then some parameters related to the pressure arch around the tunnel were analyzed. The discrete element method software PFC was used to numerically simulate the variation of shape and height of pressure arch with tunnel depth before and after an earthquake. The effect of tunnel depth, span, section shape, lining stiffness, seismic spectrum, and seismic amplitude on the shape and height of pressure arch was numerically simulated. The numerical results show that the tunnel depth, span, section shape, and seismic amplitude have great effect on the pressure arch shape, while the lining stiffness and seismic spectrum has little effect on the pressure arch shape. In addition, the shaking table tests were conducted to observe the pressure arch shape before and after an earthquake, and the experimental results were applied to verify the numerical simulation results.